Explaining the purchase pattern of utilitarian products: A case study of discount chain stores - Fatemeh Torabi; Azam Rahimi Nik; Ahmad Vedadi; Hasan Emailpour (کاوش‌های مدیریت بازرگانی, 2020)
Little is known about consumers' behavior especially when purchasing and consuming utilitarian products in developing countries. Hence, the aim of the present work is to introduce a modern and native model of consumer behavior in the selection of utilitarian products with a focus on discount chain stores. The model helps to understand and select practical marketing strategy. The data were gathered from semi-structured interviews and a review of the literature in the qualitative section of the research. A grounded theory including open coding, axial coding and selective coding was used to analyze the data. In the quantitative section of the research, the data were gathered through a questionnaire. Modeling of structural equations was also done to analyze the model. For the proposed model of consumer purchasing behavior, we found 22 factors in seven main categories including utilitarian motivations, hedonic motivations, store attributes, individual factors, functional marketing strategies, promotion and customer loyalty. The quantitative results showed that buying motivations, store attributes and marketing strategies have positive impacts on purchase intention, but gender and age have no positive impact in this regard.